Combining Nd:YAG laser with optical coherence tomography for nonsurgical treatment of basal cell carcinoma. Issue 1 (21st July 2021) - Markowitz, Orit; Bressler, Moshe Y.
Abstract: Background: Effective and aesthetically appealing management options are needed for basal cell carcinoma (BCC), the most common skin cancer. The Nd:YAG laser shows promise, but most studies use biopsy to demonstrate tumor clearance. Optical coherence tomography (OCT) could allow good tumor margin control while enabling recurrence monitoring. Objective: Determine the efficacy of the Nd:YAG laser to treat BCCs while controlling for tumor margin with OCT. Methods: A 1064‐nm Nd:YAG laser was applied to treat 119 BCCs in 102 patients, where tumor margins were approximated using OCT. Lesions were treated every 2 months until no residual tumor remained; patients were monitored for 1 year after treatment completion for clinical and subclinical recurrences. Outcomes were analyzed retrospectively. Results: Most BCCs cleared after one treatment (85/119, 70.4%). Several factors were significantly associated with a suboptimal response, that is, those with recurrence or requiring ≥2 treatments: lesion size >5 mm ( p = 0.03), focal sclerosing subtype ( p = 0.018), and immunosuppression ( p = 0.039). Midface location, patient compliance, and diagnosis method were codependent variables ( r 2 = 0.2011, p = 0.0008). All BCCs (119/119) demonstrated complete clinical and subclinical tumor clearance 2 months after final laser treatment. By 1 year, overall clinical recurrence rate (RR) was 1.7% (2/119) and cumulative subclinical RR was 4.2% (5/119). Upon excluding immunosuppressed patients, clinical RR and combined subclinical RR for primary BCC were 1% (1/98) and 2% (2/98), respectively, and 0% (0/17) and 11.8% (2/17), respectively, for recurrent BCC. Conclusions: The Nd:YAG nonablative laser can offer an effective treatment for BCCs when used with noninvasive diagnostic tools such as OCT.